Online Reviews: What Drives Consumers to Use Them. Issue 2 (4th March 2022) - Changchit, Chuleeporn; Klaus, Tim; Lonkani, Ravi
ABSTRACT: With the rapid E-commerce growth and changes in consumers' behaviors, many businesses are forced to adapt their business model to match their target customers' needs. To provide consumers with more product details and increase their confidence in making online purchases, online businesses offer online reviews as an alternative to customers physically interacting with a product. Although consumers have become familiar with the use of online product reviews, many aspects of users' perceptions of online reviews are still not well understood. This study explores the factors underlying the intention of Thai consumers to use online reviews when considering purchasing an item. The study results provide insight into the factors that affect consumers' use of online reviews prior to a purchase. This study furthers the body of knowledge that deals with online reviews and system use, providing results that allow E-businesses to adapt their business model to better fit consumers' expectations.